P2_01 Gravitation Influence on the Pole Vault - Sinclair, Jamie; Attree, Nick; Stock, Jon; Rivers, Chris (Physics Special Topics, 2011)
A recent popular web comic claimed that differences in the acceleration due to gravity across the Earth could cause a significant difference in the heights attained by identical vaults in the pole vault. This paper seeks to quantify such variation and concludes that it can be as much as 1%.